Podstawowe aspekty mariologii Sergiusza Bułgakowa - Raczyński-Rożek, Maciej (Warszawskie Studia Teologiczne, 2024)
In recent years, especially in the United States, there has been a renewed interest in the thought of the Russian theologian Sergei Bulgakov. In Poland, still few people pay attention to this original theology, and basic works must be read in foreign languages. Therefore, it seemed useful to collect and describe at least one part of his system. The article presents the main pillars of Bulgakov’s Mariology, i.e. the presentation of Mary as the Pneumatophora – the place of the personal revelation of the Holy Spirit and Mary as the chosen and perfect fruit of the human race. It also refers to the dogma of the Immaculate Conception, which became the subject of criticism of the Russian theologian, demonstrating the possibility of reconciling Bulgakov’s views with the Catholic position.